Association between nutrition intervention program indicators and stunting prevalence among toddlers in Indonesia - Syuja' Rafiqi Arifin; Ikeu Tanziha; Fatimah Zuhra; Nada Nabilla Hadi; Aripin Ahmad (AcTion: Aceh Nutrition Journal, 2025)
The prevalence of stunting in Indonesia remains high, reaching 21,6% by 2022. The government has established a stunting reduction strategy using 11 specific nutrition intervention indicators and one sensitive nutrition intervention indicator. However, the implementation of these programmes is suboptimal. This study aimed to identify the nutritional factors that influence the reduction in stunting and evaluate the effectiveness of nutrition intervention programs on the prevalence of stunting. The study utilized a cross-sectional design with Spearman correlation analysis to examine the relationship between intervention indicators and stunting prevalence, and linear regression analysis to assess their impact. The results showed significant indicators (p < 0,05) included antenatal care performed six times (r= -0,666), iron tablet supplementation for pregnant women (r= -0,362), exclusive breastfeeding (r= -0,501), growth monitoring of toddlers (r= -0,386), treatment of malnourished children (r= -0,503), complete basic immunizations (r= -0,404), adolescent health screenings (r= -0,394), adolescent iron tablet supplementation (r= -0,441), and open defecation-free villages (r= -0,448). In conclusion, increased program coverage correlated with a decrease in stunting prevalence, with antenatal care (ANC) interventions showing the strongest correlation.